Giving to the Party : the context of contributions in european democracies - Scarrow, Susan (Midwest Political Science Association, 2009)
This paper uses data from the European Social Survey to examine whether contemporary European parties benefit from cultural patterns of philanthropy, and whether tax laws seem to be an effective policy tool for encouraging contributions to political parties.